PERTANGGUNGJAWABAN PIDANA TERHADAP ADVOKAT AKIBAT SURAT PALSU YANG DIGUNAKAN KETIKA MEMBELA KEPENTINGAN HUKUM KLIEN (ANALISIS PUTUSAN NOMOR:618/PID.B/2019/PN.MDN) - Munawar Sadzali; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
Many incidents that occurred in the community against advocates who were suspected of violating the professional code of ethics were reported to Police Investigators, ignoring the examination of advocates at the Advocate Honorary Council, even though advocates have the right of immunity. The author's aim is to analyze the criminal liability of advocates due to fake letters used when defending clients' legal interests, and the application of the right of immunity against advocates when carrying out their profession, as well as the legal considerations of the Panel of Judges due to fake letters used by advocates when defending clients' legal interests. The research method used is normative legal research. Based on the results of the research, it is known that advocates who use fake letters in carrying out their profession must first be proven to have violated Article 16 of the Advocate Law, in carrying out their duties to defend their clients it is proven that there is no good faith, then they can be subject to criminal liability, and the right of immunity for advocates applies as long as it is carried out in good faith, does not violate the Indonesian Advocate Code of Ethics, and does not violate statutory regulations when carrying out professional duties inside or outside the trial court. what he used was fake, as a suggestion, it would be better if the Law on Advocates contained provisions that investigators could designate advocates as suspects after an ethics trial